Teaching English for Entrepreneurship to English Department Students at Universitas Hasyim Asy’ari (UNHASY) - Fajarina, Maskhurin; Agustina, Ria Kamilah; Daristin, Pipit Ertika; Saputra, Nopran Riyan Agung (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study explores the implementation of English for Entrepreneurship for English Department students at Universitas Hasyim Asy’ari (UNHASY). As the demand for graduates who possess both strong communication skills and entrepreneurial mindset continues to rise, integrating entrepreneurship themes into English language teaching becomes increasingly relevant. The course is designed to develop students’ ability to use English in business-related contexts such as pitching ideas, writing business plans, marketing products, and engaging in negotiations. Using a qualitative descriptive method, this research investigates students' responses, challenges, and learning outcomes through interviews, classroom observation, and document analysis. The findings show that teaching English for Entrepreneurship improves students’ confidence in motivation, critical thinking, and real-world language use, while also increasing their interest in business and self-employment. The study concludes by recommending curriculum development that combines language instruction with practical entrepreneurial skills to prepare students for the global market.